Radiation-Induced Leukoencephalopathy in Glioma Patients - Syed Faisal Nadeem,; Hania Fatima,; Zanib Javed,; Muhammad Shahzad Shamim, (Journal of the Pakistan Medical Association, 2024)
Radiation-induced leukoencephalopathy (RIL) is a late complication of cerebral radiation therapy (CRT) used in treating gliomas. It involves progressive damage to the brain's white matter, seen as T2/FLAIR hyperintensity on MRI. Risk factors include age, high radiation doses, and cumulative exposure. RIL is caused by mitochondrial dysfunction, blood-brain barrier disruption, and oligodendrocyte apoptosis, leading to neurocognitive decline, ranging from mild memory issues to severe dementia. While no cure exists, treatment focuses on managing symptoms, and research is exploring ways to minimize risk through lower radiation doses and targetted therapies. This review aims to summarize key findings on RIL, focusing on its epidemiology, pathogenesis, clinical manifestations, and existing treatments. Keywords: Radiation-induced leukoencephalopathy, Radiation, Glioma, Degeneration, Oligodendrocyte.